Accuracy and Safety of Fluoroscopic Guided Percutaneous Pedicle Screws in Thoracic and Lumbosacral Spine: A Review of 2000 Screws. Issue 17 (1st September 2015) - Hansen-Algenstaedt, Nils; Chiu, Chee Kidd; Chan, Chris Yin Wei; Lee, Chee Kean; Schaefer, Christian; Kwan, Mun Keong
Abstract : Study Design: Retrospective study. Objective: To investigate the accuracy and safety of percutaneous pedicle screws placed using fluoroscopic guidance in the thoracic and lumbosacral spine. Summary of Background Data: Several studies had examined the accuracy and safety of percutaneous pedicle screws but provided large variations in their results with small number of patients or few number of pedicle screws evaluated. Methods: Computerized tomography of patients who had surgery with fluoroscopic guided percutaneous pedicle screws were chosen from 2 centers: (1) European patients from University Medical Center Hamburg-Eppendorf, Germany and (2) Asian patients from University Malaya Medical Centre, Malaysia. Screw perforations were classified into Grade 0, Grade 1 (<2 mm), Grade 2 (2–4 mm), and Grade 3 (>4 mm). Results: In total, 2000 percutaneous pedicle screws from 273 patients were analyzed: 1290 screws from 183 European patients and 710 screws from 90 Asian patients. The mean age was 59.1 ± 15.6. There were 140 male patients and 133 female patients. The total perforation rate was 9.4% with 151 (7.5%) Grade 1, 31 (1.6%) Grade 2, and 5 (0.3%) Grade 3 perforations. The total perforation rates among Europeans were 9.4% and among Asians were 9.3%. There was no difference between the 2 groups ( P > 0.05). There were 3 distinct peaks in perforation rates (trimodal distribution) at T1, midthoracic region (T4–T7), and lumbosacral junction (L5 and S1). The highest perforation rates were at T1 (33.3%), S1 (19.4%), and T4 (18.6%). Conclusion: Implantation of percutaneous pedicle screws insertion using fluoroscopic guidance is safe and has the accuracy comparable to open techniques of pedicle screws insertion. Level of Evidence: 4 Abstract : This computed tomography study investigates the accuracy of 2000 thoracic and lumbosacral percutaneous pedicle screws placed in Europeans and Asians. The total perforation rate was 9.4% with 7.5% Grade 1, 1.6% Grade 2, and 0.3% Grade 3 perforations. Fluoroscopic guided percutaneous pedicle screws placement has the accuracy and safety comparable to the conventional open method.